SISTEM BAHASA MASYARAKAT BADUY LUAR - Kurniasih, Dedeh; Encep Supriatna; Sapriya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore and examine the local wisdom of the language system among the Baduy community living in Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province. A qualitative descriptive method was used as the research approach. Local wisdom is explored as the foundation of this study, specifically to understand the language system of the Baduy community. Data collection was carried out through observation, documentation, and interviews with several informants. Data analysis was conducted qualitatively through data reduction, data presentation, and drawing conclusions. The research findings show that Baduy language is one of the regional languages in Indonesia and is fairly preserved by the local government, although linguistic studies on this language remain limited. The use of Baduy language is considered an important marker of ethnic identity for the Baduy community. Although the Baduy people are an isolated community, many of them are bilingual, meaning they can also communicate in Indonesian in their daily lives, especially when interacting with people from outside the Baduy area who visit their territory.